Diplomatic Documentation of the Crimean Khanate in the 16th century (1515–1596): To the Question about the Current State of Publishing » - A.V. Vinogradov (Золотоордынское обозрение)
Research objectives: to outline the key issues of the current state of publication of diplomatic documents containing information about the Crimean Khanate’s relations with Russian and Polish-Lithuanian states during the period of 1515–1596. Research materials: the Crimean diplomatic documents and letters of the Crimean khans Muhammad Giray I, Saadet Giray, Islam Giray I, Sahib Giray, Devlet Giray I, Mohammed Giray II, Islam Giray II and Gazi Giray II to the Moscow princes and Polish kings preserved in the archives and library manuscript collections in Russia and Poland. Research results: as a result of research the author has introduced into scholarly circulation a generic list of (both published and unpublished) messages of the Crimean khans to the Polish kings and princes of Moscow for the period of 1515–1596 preserved in the archives and library manuscript collections in Russia and Poland. Research novelty: the author is the first to consider the problem of the publication of diplomatic documents of the Crimean Khanate being a part of the Crimean ambassadorial books in the fund 123 (“Russian relations with the Crimea”) of Russian State Archive of Ancient Acts.